Gender Recognition and Age-group Prediction: A Survey (International Journal of Engineering and Computer Science, 2014)
Over the recent years, a great deal of effort has been made to age estimation & gender recognition from face images. It has been reported that age can be accurately estimated under controlled environment such as frontal faces, no expression, and static lighting conditions. However, it is not straightforward to achieve the same accuracy level in real-world environment because of considerable variations in camera settings, facial poses, and illumination conditions. In this paper, we discuss different method to estimate age and gender predication.